Exploring English Language Teaching: Language in Action: Graham Hall. New York/Oxon: Routledge, Segunda Edición, 2018, 313 páginas. - Singer, Néstor (Arboles y Rizomas, 2020)
Reseña el libro Exploring English Language Teaching: Language in Action de Graham Hall.